The Use of Minilocked Plate for Management of Unstable Metacarpal Fractures - AL-Madawy, Ahmed Mohammed; Elatta, Mohamed Mahmoud Abou; Hasanin, Mostafa Mahmoud; Al-Nahal, Ashraf Abd El-Kader (Journal of Hand and Microsurgery, 2016)
Objective This study aims to evaluate the use of minilocked plates in the treatment of the metacarpal fractures.Method A total of 30 patients of metacarpal fractures were treated by minilocked plates.Results Union was achieved in all patients. There were 27 (90%) patients having satisfactory results (excellent and good results) and 3 patients (10%) had poor results.Conclusion The use of minilocked plate is recommended for fixation of periarticular, comminuted, and osteoporotic metacarpal fractures that offer rigid fixation early mobilization, decreases the incidence of joints stiffness, and tendon adherence which maximized the hand function.
Keywords: metacarpal fracture; locked plates; miniplate